2013
DOI: 10.1007/s11745-013-3859-2
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cyclooxygenase Products are Higher and Lipoxygenase Products are Lower in Early Disease in the pcy Mouse Model of Adolescent Nephronophthisis

Abstract: Nephronophthisis (NPHP) is a pediatric form of hereditary polycystic kidney disease (PKD), and is the leading cause of end stage renal disease in children. The pcy mouse is an orthologous model of human NPHP, with a mutation in the Nphp3 gene. Renal phospholipase A2, cyclooxygenase (COX) 1 and cyclic AMP are elevated in this model, suggesting that eicosanoid formation may be altered. In another type of PKD observed in the Han:SPRD-Cy rat, inhibition of eicosanoid production slows disease progression. If renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Kidney COX derived oxylipins are up-regulated in the pcy mouse model by as early as 30 days of age [7]. A similar elevation of renal COX oxylipins is observed in the Han:SPRD-Cy rat, a related model of slowly progressive kidney cyst formation [21,25], and reduction of COX oxylipins via pharmacological or dietary interventions have been shown to reduce disease progression [21,[26][27][28].…”
Section: Effect Of Dietary Flax Oil On Cox Oxylipins In Diseasementioning
confidence: 75%
See 1 more Smart Citation
“…Kidney COX derived oxylipins are up-regulated in the pcy mouse model by as early as 30 days of age [7]. A similar elevation of renal COX oxylipins is observed in the Han:SPRD-Cy rat, a related model of slowly progressive kidney cyst formation [21,25], and reduction of COX oxylipins via pharmacological or dietary interventions have been shown to reduce disease progression [21,[26][27][28].…”
Section: Effect Of Dietary Flax Oil On Cox Oxylipins In Diseasementioning
confidence: 75%
“…Our previous studies on the pcy mouse, as well as on a related model of cystic kidney disease (the Han:SPRDCy rat), revealed that cytosolic phospholipase A 2 and COX protein levels are altered in diseased cystic kidneys [6]. Further studies showed that COX products from arachidonic acid (AA) are elevated and LOX products from both AA and linoleic acid (LA) are lower in pcy mouse kidneys compared to those of normal kidneys as early as 30 days of age [7]. Renal COX products such as PGI 2, PGE 2 and PGD 2 may play a role in the development of cystic disease, as they increase renal cAMP [8], which is elevated in kidney, cyst fluid and urine of pcy mice as young as 45-70 days of age [9].…”
Section: Introductionmentioning
confidence: 99%
“…TXA2 stimulates cell proliferation in culture, and is a potent vasoconstrictor. In addition, TXA2 synthase inhibitors reduce progressive glomerular destruction in rat kidneys [134,135]. Another oxylipin, 20-HETE, produced from AA is an effective vasoconstrictor and mediates inflammation [136].…”
Section: Oxylipins In Kidney Liver and Serummentioning
confidence: 99%
“…Dysregulation of cAMP signaling is a common feature of CKD. In ADPKD and infantile NPH mouse models, renal cAMP levels are increased and associated with increased proliferation and cyst formation (43,44). In contrast, cAMP signaling cascade is decreased in several models of renal fibrosis (45).…”
Section: Ciliogenesis and Campmentioning
confidence: 99%